2019
DOI: 10.1038/s41598-019-55375-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of key pathways in rat liver after a one-year feeding trial with transgenic maize MON810

Abstract: In a recent one-year feeding study, we observed no adverse effects on tissue level in organs of rats fed with the genetically-modified maize MON810. Here, we assessed RNA expression levels of 86 key genes of the apoptosis-, NF-кB-, DNA-damage response (DDR)-, and unfolded-protein response (UPR) pathways by RT-qPCR in the rat liver. Male and female rats were fed either with 33% MON810 (GMO), isogenic- (ISO), or conventional maize (CONV) and RNAs were quantified from eight rats from each of the six feeding group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…These results are in accordance with those of Rhee et al ., 21 who demonstrated that the consumption of GMPs did not have negative effects on the fertility of rats. The absence of adverse effects in our study are consistent with those described in other studies in which processed GM crops with enhanced agronomic traits have shown the absence of clinical effects or histopathological abnormalities in the organs or tissues of animals 22‐37 . Other safety assessment studies of GMPs showed the absence of negative effects on rats 19,38,39 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with those of Rhee et al ., 21 who demonstrated that the consumption of GMPs did not have negative effects on the fertility of rats. The absence of adverse effects in our study are consistent with those described in other studies in which processed GM crops with enhanced agronomic traits have shown the absence of clinical effects or histopathological abnormalities in the organs or tissues of animals 22‐37 . Other safety assessment studies of GMPs showed the absence of negative effects on rats 19,38,39 .…”
Section: Discussionsupporting
confidence: 92%
“…The absence of adverse effects in our study are consistent with those described in other studies in which processed GM crops with enhanced agronomic traits have shown the absence of clinical effects or histopathological abnormalities in the organs or tissues of animals. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Other safety assessment studies of GMPs showed the absence of negative effects on rats. 19,38,39 In contrast, in some cases, side effects have been detected in GMP-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…While it must be stressed that some of the concerns raised about GM crops are founded and should be addressed prior to release, a lot of the opposition is either out of ignorance or it is outright manipulative. For example, as discussed in this review, there are claims that GM crops adversely affect humans and animals [81], yet there is no empirical data supporting this assertion. Furthermore, suggestions that transgenes will contaminate the environment appear to assume that transgenes, including those derived from virus genomes, are by their nature harmful to the environment.…”
Section: Discussionmentioning
confidence: 92%
“…The possible adverse effects of transgenes to humans and animals, as well as to the plants have been expressed. However, an investigation of GM maize in rats either showed no negative effect [81] or the toxicity observed was due to herbicides that were used to control weed in the experiments, and not to the transgene [81,82]. With regards to GE for virus resistance, most viral resistance transgenes are designed from viral genes or segments, which are also present in foods from infected non-GM crops.…”
Section: Toxicity Of Transgenementioning
confidence: 99%